Effect of pruning severity and nitrogen levels on yield and quality of Phalsa (Grewia subinequalis D.C.) under sodic soil conditions of Lucknow - Chaturvedi, S.K.; Ram, R.B.; Meena, M.L. (Indian Journal of Agroforestry, 2020)
An experiment was conducted on sodic soil at Horticulture Research Farm of Department of Applied Plant Science (Horticulture), Babasaheb Bhimrao Ambedkar University, Rae Bareli Road, Lucknow during the year 2007-08 and 2008-09 with four levels of pruning (P0-control, P1-30 cm, P2-60 cm and P3-90 cm above the ground level) and four levels of nitrogen (N0-control, N1-40 g, N2-80 g and N3,-120g/plant). The observations recorded based on two year’s 2007- 08 and 2008-09 experiment. It has been observed that average number of fruits per plant (1576.47 and 1380.53) and yield per bush (0.850 and 0.800 kg) were highest in treatment P3N2.However, the highest 100 fruit weight (66:25 and 57.20 g) was recorded with P1N2. Highest TSS (17.40 and 18.00%) was recorded under the PA and acidity (3.85 and 5.00%) in P2N1 while, it was least (2.90 and 3.25%) in P3N0. Percentage of Ascorbic acid was highest (39.80 and 37.50 mg/100 g fresh fruit weight) in treatment combination P2N2. The juice and total sugar per cent was recorded highest (55.60, 50.60 and 15.25,14.80%) in treatment combination P,N2 and reducing sugar (12.2 and 12.8%) in P3N2.In overall performance, P3N2 was the best treatment combination.